2015
DOI: 10.1186/s13053-015-0040-3
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of BRCA1 founder mutation c.5266dupC (5382insC) in breast cancer patients from Ukraine

Abstract: Germ-line mutations in several genes, such as BRCA1 and BRCA2, are known to increase the risk of breast cancer. These heritable mutations are unequally represented among populations with different ethnic background due to founder effects and thereby contribute to differences in breast cancer rates in different populations. The BRCA1 mutation c.5266dupC (also known as 5382insC or 5385insC) was detected in a sample of 193 breast cancer patients in Ukraine by multiplex mutagenically separated PCR using published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…Indeed, our data indicate the absence of hot-spot mutation except BRCA1 5382insC, but a very strong prevalence of this mutation in early onset cancer patients (87.5 % of all found BRCA1 mutations). A frequency of the BRCA1 5382insC mutation among non-selected breast cancer patients in Russia was reported in several studies [4,12,14]. Similar frequency of the BRCA1 5382insC mutation was reported for Ukranian breast cancer patients [15].…”
Section: Resultssupporting
confidence: 75%
“…Indeed, our data indicate the absence of hot-spot mutation except BRCA1 5382insC, but a very strong prevalence of this mutation in early onset cancer patients (87.5 % of all found BRCA1 mutations). A frequency of the BRCA1 5382insC mutation among non-selected breast cancer patients in Russia was reported in several studies [4,12,14]. Similar frequency of the BRCA1 5382insC mutation was reported for Ukranian breast cancer patients [15].…”
Section: Resultssupporting
confidence: 75%
“…Although these pathogenic mutations were first identified in Ashkenazi Jews, BRCA1 c.5266dupC, was later described in other populations. It has already been identified in many countries of Central and Eastern Europe (Burcos et al, 2013;Gorodetska et al, 2015) and also recurrently described in the Brazilian population (Lourenço et al, 2004;da Costa et al, 2008;Fernandes et al, 2016), representing 20% of the BRCA1 pathogenic variants reported in a recent survey (Palmero et al, 2018).…”
mentioning
confidence: 75%
“…Another example is the increased frequency of the c.5266dupC mutation (referred to as 5382insC in the cited publications) in the BRCA1 gene in European part of Russia, which is responsible for 10% to 17% of cases of breast and ovarian cancer [75,76]. e same phenomenon is also observed in some Eastern European countries with a predominantly Slavic population neighboring Russia, in particular in Ukraine [77] and Belarus [78]. Comparing the cost of two-stage testing in these populations against a general NGS-based approach, the cost of targeted NGS panels for the diagnosis of hereditary PC per analysis for one patient ranges from $250 to $1,500, depending on how many loci are included in the panel in addition to BRCA1/2 [69].…”
Section: Molecular Geneticmentioning
confidence: 84%